Analisis Motivasi Kerja pada Dinas Tanaman Pangan Hortikultura dan Peternakan dengan Pengaruh Kompensasi serta Disiplin Kerja - Raynaldo Listianov (Journal of Business and Economics (JBE) UPI YPTK, 2022)
This study aims to determine the effect of compensation and discipline on employee performance through work motivation as an intervention variable at the Department of Horticulture and Animal Husbandry. The method used is multiple linear regression analysis and path analysis. by distributing a questionnaire of 70 respondents. The results obtained that there is a positive and significant effect of compensation on work motivation at the Department of Horticulture and Animal Husbandry. There is a positive and significant effect on work motivation at the Department of Horticulture and Animal Husbandry. There is a positive and significant influence on the performance of employees at the Department of Horticulture and Animal Husbandry. There is a positive and significant influence on the performance of employees at the Department of Horticulture and Animal Husbandry. There is a positive and significant effect of work motivation on employee performance at the Department of Food Crops, Horticulture, and Animal Husbandry. Work motivation mediates the effect of compensation on employee performance at the Department of Food Crops, Horticulture, and Animal Husbandry. Work motivation mediates the effect of discipline on employee performance at the Department of Food Crops, Horticulture, and Animal Husbandry.